The Performance of Recycled Fine Aggregate Foamed Concrete Incorporating Ground Granulated Blast Furnace Slag-Steel Slag - Zhang, Bo (International Journal of Materials Science and Technology Studies, 2025)
To address the low utilization rates of discarded concrete and industrial solid wastes, this study developed a novel foam concrete (FC) incorporating ground granulated blast furnace slag (GGBS), steel slag (SS), and cement as binders, with natural river sand blended with carbonized recycled fine aggregate (CRFA) as fine aggregates, and reinforced with modified basalt fiber (MBF). FC can be used to backfill voids in underground projects, which not only reduces the overall weight of the building, but also insulates and saves energy. Initially, a univariate experiment determined the optimal CRFA replacement rate and MBF content. Subsequently, the effects of GGBS and SS on the mechanical and physical properties of FC were investigated. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses revealed a synergistic hydration mechanism between GGBS and SS. The results showed that a 20% CRFA replacement and 4 kg·m-3 MBF produced maximum compressive and flexural strengths while reducing thermal conductivity. Additionally, the simultaneous addition of GGBS and SS decreased CH content and refined the pore structure, yielding a more uniform distribution with fewer connected pores. When both GGBS and SS were incorporated at a 20% replacement level, the 28-day compressive and flexural strengths peaked, and thermal conductivity decreased with increasing slag ratios. These findings confirm the synergistic hydration phenomenon of GGBS and SS and offer theoretical guidance for the engineering application of FC.